A key to the species of genus Synochoneura Obraztsov, 1955 (Lepidoptera: Tortricidae) from China with the descriptions of a new species from Wuyishan National Park - Liang, Teng-Da; Mo, Shi-Fang; Wang, Min; Wang, Chen-Bin (Zootaxa, 2023)
A new species of the genus Synochoneura Obraztsov, 1955, S. wuyishana sp. nov. is described and illustrated from Wuyishan National Park in Fujian Province of China. The new species resembles S. sapana, but differs in wing pattern and female genitalia characters. Illustrations of adults and genitalia are provided. Additionally, a key to the Chinese Synochoneura species based on morphology is presented. The type specimens are deposited in the Department of Entomology, College of Plant Protection, South China Agricultural University, Guangzhou.